2016
DOI: 10.2208/kaigan.72.i_1273
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Year Analysis on Circulation and Associated Larval Transport in the Seto Inland Sea, Japan

Abstract: 2 正会員 神戸大学教授 大学院工学研究科市民工学専攻(〒657-8501 兵庫県神戸市灘区六甲台町1-1)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…The reason for the difference in 137 Cs distribution between the models with and without tidal forcing is that enhanced vertical mixing by tides retards the 137 Cs dilution. These retardations of offshore material transport and dilution due to the coastal flows, small eddies, and tides are consistent with the findings of previous studies [7,8,14]. Figure 9 shows the area-averaged surface K e , depth-averaged vertical velocity variance, and depthintegrated 137 Cs concentration variance averaged over the area displayed in Figures 4-8 intensifies oceanic fluctuations and the resultant mixing, while the ROMS-L2 (w/tide) results show the contribution of tidal forcing.…”
Section: Effects Of Downscaling and Tidesupporting
confidence: 89%
See 1 more Smart Citation
“…The reason for the difference in 137 Cs distribution between the models with and without tidal forcing is that enhanced vertical mixing by tides retards the 137 Cs dilution. These retardations of offshore material transport and dilution due to the coastal flows, small eddies, and tides are consistent with the findings of previous studies [7,8,14]. Figure 9 shows the area-averaged surface K e , depth-averaged vertical velocity variance, and depthintegrated 137 Cs concentration variance averaged over the area displayed in Figures 4-8 intensifies oceanic fluctuations and the resultant mixing, while the ROMS-L2 (w/tide) results show the contribution of tidal forcing.…”
Section: Effects Of Downscaling and Tidesupporting
confidence: 89%
“…Another important factor that should be considered in STEAMER is tide, which MOVE and RTOFS-Global do not consider. Kosako et al (2016) [8] conducted Lagrangian particle tracking in the Seto Inland Sea, where the Ikata nuclear power plant is located. Their sensitivity experiments focusing on tidal influences demonstrated that material transport toward the offshore direction was largely suppressed by vertical mixing due to tides; thus, the usage of nontidal MOVE and RTOFS-Global as input data for STEAMER may lead to overestimation of offshore material transport in tidal-flow-dominated waters.…”
Section: Introductionmentioning
confidence: 99%